AN OBSERVATIONAL STUDY OF ENTHESOPATHY IN DRIED HUMAN SCAPULAE - AGARWAL, SUMITA; MOTAGI, MANJUNATH V; PAL, VISHNU; VAIDYA, YUGANTI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: An abnormal ossification process in soft tissues at the attachment site to a bone is called enthesopathy due to biomechanical movements of bone. The present study aimed to observe the calcification of the transverse scapular ligament (TSL) with complete or partial ossification, the presence of the triangular bony growth at the lateral border of scapula and to observe vascular foramen/foramina piercing at the bases of the spine of scapulae. Methods: An observational study was conducted on dried human scapulae 140 in number (70 right and 70 left) of unknown sex and age, procured from the Department of Anatomy, People’s College of Medical Science and Research Center, Bhopal, and Government Doon Medical College, Dehradun, India. These scapulae were studied to observe enthesopathic changes in them. Measurements were taken with Vernier calipers. Results: In the present study, we observed the presence of completely ossified TSL with formation of complete suprascapular foramina in 8.57% scapulae. The incidence of triangular bony growth at the lateral border of scapula was found in 40% scapulae of the right side and 32.85% of the left. The incidence of vascular foramina piercing at the bases of the spine of scapulae was 17.14% on the right side and 21.42% on the left side scapulae. Conclusion: The study provides the descriptive knowledge of enthesopathy in scapulae. The study is of great significance for neurosurgeons and orthosurgeons to carry out various reconstructive surgeries.